2020
DOI: 10.17263/jlls.803551
|View full text |Cite
|
Sign up to set email alerts
|

Lexical measures for testing progress in Hebrew as Arab students’ L2

Abstract: Since Ure (1971) and Halliday (1985), different measures have been proposed in the research literature as a proxy for investigating lexicon advances. They are called lexical richness measures and are an important tool in assessing advance of the lexicon (Johansson, 2009). This article evaluates three lexical richness measures of progress in the acquisition of Hebrew by Arab students in Israel: level of abstractness, lexical diversity, and density lexical. The corpus consisted of sixty essays written in Hebrew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The communication of the sensory experience of the character in shape of traces that the environment leaves on his consciousness avoids intrusion from the position of the privileged speaker even in cases when the lexical choice does not belong to the character (Muhaxheri, 2021;Abu, 2020).…”
Section: The Efforts To Revitalize the Languagementioning
confidence: 99%
“…The communication of the sensory experience of the character in shape of traces that the environment leaves on his consciousness avoids intrusion from the position of the privileged speaker even in cases when the lexical choice does not belong to the character (Muhaxheri, 2021;Abu, 2020).…”
Section: The Efforts To Revitalize the Languagementioning
confidence: 99%
“…Therefore, at fundamental levels, a gap of one year is enough to assess a change in the lexicon, while a more extended period is needed at advanced levels. It has been found that lexicon development patterns are not always prominent if one does not look at long-term development (Abu-Rabiah, 2017, 2020a, 2020b, 2022. Second, in some studies, older students use their writing within a limited but very familiar vocabulary or "playing it safe", which lowers the lexical diversity in their writing (Laufer, 1991).…”
Section: Lexical Diversitymentioning
confidence: 99%
“…The chief merit of quantitative analysis is that it is objective (Abu Rabiah, 2020). Besides, it can deal with large datasets effectively and rapidly.…”
Section: Literature Reviewmentioning
confidence: 99%